La familia en la construcción de identidad en los adolescentes de 10 a 19 años del distrito de Pacanga, provincia de Chepén en el 2017 - Hernández Vigo, Segundo Roberto (2017)
This thesis report refers to LA FAMILIA EN LA CONSTRUCCIÓN DE IDENTIDAD EN LOS ADOLESCENTES DE 10 A 19 AÑOS DEL DISTRITO DE PACANGA, PROVINCIA DE CHEPÉN EN EL 2017,Is referred to adolescent residents in the district of Pacanga, Province of Chepén; In which a total of 45 adolescents between the ages of 10 and 19 participated. The present research work is about the main factors that influence to shape a personality and how it is generated within a being that is constantly changing. Likewise, the main distractors that direct the teenager to choose traits and characteristics for the creation of their identity are mentioned. So also through the conduct of research as society becomes an important factor for the formation of the identity of adolescents, because as we know the relatives, friends and people close to them, are the ones who are going to To guide the adolescent to acquire an identity, but we must take into account that when they go through the stage of adolescence are very easy to mold and therefore can suddenly change decision. In addition, adolescents redefine their role in society through the construction of their social identity, based on the values, beliefs, customs, behaviors and thoughts instilled by families, as well as knowing the learning processes that Are given inside and outside the home through peer groups.